STUDY OF THE ASSOCIATION OF POLYMORPHISMS OF CALCIUM METABOLISM AND BONE HOMEOSTASIS GENES WITH THE RISK OF ATHEROSCLEROSIS IN PATIENTS WITH GENERALIZED PERIODONTITIS - Babenia, H.O.; Dienha, O.V.; Shnaider, S.A.; Nikolayeva, G.V.; Korniichuk, O.E.; Dorohina, O.S. (World of Medicine and Biology, 2025)
Genotyping of single nucleotide polymorphisms of several genes of calcium metabolism and bone homeostasis in patients with generalized periodontitis on the background of atherosclerosis atherosclerosis and in the control group was carried out. The association of the A allele of the rs6252 polymorphism of the PTH (parathyroid hormone) gene with the risk of atherosclerosis was revealed: OR=3.857 (95 % CI 1.243-11.968), the reliability of the χ2 value p=0.017. The homozygous AA genotype of this polymorphism was also associated with an increased risk of atherosclerosis in a recessive inheritance model (p=0.035). The experimental and control groups did not differ significantly in the distribution of frequencies of genotypes and alleles of polymorphisms rs1544410 of the VDR gene (vitamin D receptor), rs1801725 of the CASR gene (calcium-sensitive receptor), rs1126616 of the SPP1 gene (osteopontin), rs1801197 1377 C>T of the CTR gene (calcitonin receptor) and rs1801133 of the MTHFR gene (methylenetetrahydrofolate reductase).